A Review on Ethnicity and Type 2 Diabetes in Pacific Adults in New Zealand - Ljiljana M. Jowitt (Recent Updates in Disease and Health Research Vol. 8, 2024)
This review presented ethnic characteristics of type 2 diabetes in Pacific Island adults in New Zealand. Diabetes mellitus is one out of four non-communicable diseases (NCDs), which represents a set of metabolic disorders with chronic hyperglycaemia due to defects of insulin secretion, insulin action, or both. If left untreated or undiagnosed, diabetes mellitus leads to confusion, coma, or death due to ketoacidosis. Pacific Island people in New Zealand with a specific Polynesian phenotype originate from the islands in the Pacific Ocean such as Samoa, the Cook Islands, Tonga, Niue, Tokelau, Papua New Guinea, Vanuatu, Kiribati, Fiji, Solomon Islands, Nauru, and French Polynesia. Therefore, they may have similar genetic and cultural origins. Pacific Island populations were attracted to New Zealand by the prospect of employment and were welcomed as a solution to workforce shortages in unskilled and semi-skilled occupations. About 42% of the Pacific population live in the 10% most deprived areas of the country, with poorer housing and overcrowding, which suggests that the incidence of diabetes is higher for people living in the most deprived areas, compared with people living in the least deprived areas. Socioeconomic inequalities, low education and unemployment create remarkable psychological distress. Changes in diet rich in sugars, tobacco use, and harmful use of alcohol have resulted in a profound reduction in physical activity and increased obesity rates in adults and children. The "thrifty genotype" hypothesis can explain the current increase in the prevalence of obesity in New Zealanders of Polynesian descent. Obesity and type 2 diabetes are major challenges for Pacific Island adults, and they still have comparatively higher rates of obesity (68%) and diagnosed diabetes (13%), ten years earlier than any other ethnic group in New Zealand. Overweight and obesity have been linked to lower serum 25-OHD concentrations, impaired insulin action, glucose metabolism, and various metabolic processes in adipose and lean (muscle) tissue. Central or visceral fat is more metabolically active than subcutaneous fat, causing dysmetabolism of fatty acids and increased influx of free fatty acids into the splanchnic circulation. Besides storing fat, adipose tissue releases molecules commonly referred to as adipokines which may support \(β\)-cell failure and the development of type 2 diabetes in Pacific people. Antihypertensive and anti-lipid (statin) therapy was lowest among Pacifica people. The blood levels of triglycerides were the lowest in the Pacific population. However, HbA1C was significantly higher among Pacific people than among Maori, who had higher HbA1C than New Zealand Europeans. Interestingly, as a group, Pacific Island populations are neither hyperinsulinaemic nor insulin-resistant using HOMA-IR. This Polynesian phenotype is linked to the metabolic disorders of gout and type 2 diabetes mellitus, due to the presence of visceral obesity owing to its strong association with insulin resistance, metabolic syndrome, type 2 diabetes, and cardiovascular disease.